2016
DOI: 10.1016/j.jvs.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of arteriovenous fistulas and grafts with or without intervention before successful use

Abstract: Objective Arteriovenous fistulas (AVF) are considered superior to arteriovenous grafts (AVG) because of longer secondary patency after successful cannulation for dialysis. We evaluated whether access interventions before successful cannulation impact the relative longevity of AVF and AVG after successful use. Methods This retrospective study of a prospective database identified patients who initiated dialysis with a catheter, and subsequently had a permanent access (289 AVF and 310 AVG) placed between 1/1/06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 28 publications
6
87
2
Order By: Relevance
“…There are several issues that have grown out of the push to increase AVF utilization that might explain this. In addition, multiple studies (22)(23)(24) have shown that a salvaged FTM-AVF requires additional interventions to maintain its patency. However, if all AVFs that are created are considered, the primary patency of AVFs and AVGs is comparable for the first year after creation because of AVF FTM (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…There are several issues that have grown out of the push to increase AVF utilization that might explain this. In addition, multiple studies (22)(23)(24) have shown that a salvaged FTM-AVF requires additional interventions to maintain its patency. However, if all AVFs that are created are considered, the primary patency of AVFs and AVGs is comparable for the first year after creation because of AVF FTM (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It is not our intent to review factors implicated in these outcomes but only to provide some brief trends and facts. Autologous AVFs have better survival than synthetic AVGs considering both primary and secondary-assisted patency [48][49][50]. Median technical survival with AVFs ranges between 3 and 10 years compared to AVGs which range between 1 and 4 years.…”
Section: Va Performance and Outcomementioning
confidence: 99%
“…When an AVF is created in an obese patient, it frequently requires a subsequent transposition procedure to make it accessible for cannulation by the dialysis staff (26). A recent analysis from our center found that, as compared to AVFs that were cannulated without a prior intervention, those that required a transposition surgery had a shorter cumulative AVF patency and required more frequent interventions to maintain long-term patency for dialysis after successful cannulation (28). Placement of an AVG rather than an AVF in this population permits a single surgical procedure, faster access cannulation, and shorter catheter-dependence.…”
mentioning
confidence: 99%